Development and performance of a 2.9 Tesla dipole magnet using high-temperature superconducting CORC® wires. (7th December 2020) - Wang, Xiaorong; Abraimov, Dmytro; Arbelaez, Diego; Bogdanof, Timothy J; Brouwer, Lucas; Caspi, Shlomo; Dietderich, Daniel R; DiMarco, Joseph; Francis, Ashleigh; Garcia Fajardo, Laura; Ghiorso, William B; Gourlay, Stephen A; et al.
Abstract: Although the high-temperature superconducting (HTS) REBa2 Cu3 O x (REBCO, RE–rare earth elements) material has a strong potential to enable dipole magnetic fields above 20 T in future circular particle colliders, the magnet and conductor technology needs to be developed. As part of an ongoing development to address this need, here we report on our CORC ® canted cos θ magnet called C2 with a target dipole field of 3 T in a 65 mm aperture. The magnet was wound with 70 m of 3.8 mm diameter CORC ® wire on machined metal mandrels. The wire had 30 commercial REBCO tapes from SuperPower Inc. each 2 mm wide with a 30 µ m thick substrate. The magnet generated a peak dipole field of 2.91 T at 6.290 kA, 4.2 K. The magnet could be consistently driven into the flux-flow regime with reproducible voltage rise at an engineering current density between 400–550 A mm −2, allowing reliable quench detection and magnet protection. The C2 magnet represents another successful step towards the development of high-field accelerator magnet and CORC ® conductor technologies. The test results highlighted two development needs: continue improving the performance and flexibility of CORC ® wires and develop the capability to identify locations of first onset of flux-flow voltage.